MODAL SOSIAL KELOMPOK TANI BUDI MARGOMULYO II DALAM PEMENUHAN KEBUTUHAN SUMBERDAYA EKONOMI USAHATANI PADI (Studi Kasus Di Desa Pontang Kecamatan Ambulu Kabupaten Jember) - Frida Dewi Alfina Rahmah; Diah Puspaningrum (Universitas Andalas, 2021)
The Budi Margomulyo II Farmer Group is a farmer group located in Pontang Village, Ambulu District, Jember Regency who has problems related to the availability of economic resources in rice farming. This study was aimed to determine existing social capital in the Budi Margomulyo II Farmer Group in meeting economic resources needs in terms of resource components, social structure, and actions at the micro and meso levels. The location selection is determined purposively (purposive method), on the reasoning that there is a good potential in the agricultural sector and that Budi Margomulyo Farmer Group is an active farmer group with various achievements and has succeeded in becoming one of the pioneers in establishing a union. This research is qualitative research with purposive sampling used while choosing the informants. Data analysis of this research employed the Interactive Method of Miles and Huberman. The results showed that the economic resource needs of group members can be met with the existence of social capital in the farmer group both at the micro and meso levels